The Role of Womenpreneurs on the Income of MSMEs and Economic Growth in South Sulawesi Through Digital Marketing - Dewi, Riska; Sulfiana, Sulfiana; Salim, Agus (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to examine the influence of the role of womenpreneurs on the income of Micro, Small and Medium Enterprises (MSMEs) and the economic growth of South Sulawesi. Regression 1 dependent variable in this study is the role of womenpreneur and digital marketing and the independent variable is the income of Micro, Small and Medium Enterprises (MSMEs) with a total sample of 60 MSMEs in South Sulawesi taken from indirect (online) and direct (offline) questionnaire surveys. While regression 2 dependent variables in this study are the role of womenpreneurs and the independent variable is the economic growth of South Sulawesi from 2014-2024. The method used is the multiple linear regression analysis method with the help of Eviews 10 software including classical assumption tests, statistical T tests and statistical F tests. The results of the study indicate that the role of womenpreneurs and digital marketing have a significant positive effect on the income of MSMEs and have a significant positive effect on the economic growth of South Sulawesi. This indicates that there are positive impacts on women's empowerment such as increased self-confidence, social change, increased income, digital marketing knowledge and contribution to the local economy.